2019
DOI: 10.1103/physrevresearch.1.033161
|View full text |Cite
|
Sign up to set email alerts
|

Genuine photon-magnon-phonon Einstein-Podolsky-Rosen steerable nonlocality in a continuously-monitored cavity magnomechanical system

Abstract: In this paper, we propose a scheme for generating genuine tripartite steering nonlocality in a cavity magnomechanical system composed of an yttrium iron garnet (YIG) sphere with a diameter of a few hundred micrometers inside a microwave cavity. In the system, the magnons, i.e., collective spin excitations in the sphere, are coupled to the cavity photons via magnetic-dipole interaction and at the same time coupled to phonons, the quanta of vibration of the sphere, by magnetostrictive interaction. We consider th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 49 publications
(16 citation statements)
references
References 43 publications
0
16
0
Order By: Relevance
“…These protocols [15][16][17]33] essentially utilize the nonlinear magnetostrictive interaction effectively activated by properly driving the magnon mode with a magnetic field, which can be experimentally realized by directly driving the YIG sphere with a small MW loop antenna [34], allowing to implement the magnomechanical beamsplitter or two-mode squeezing interactions. Other quantum effects like tripartite Einstein-Podolsky-Rosen steering have also been studied [35]. In addition, many other interesting topics have been explored in CMM, including magnetically tunable slow light [36], phonon lasing [37], thermometry [38], and parity-time-related phenomena [39][40][41].…”
Section: Introductionmentioning
confidence: 99%
“…These protocols [15][16][17]33] essentially utilize the nonlinear magnetostrictive interaction effectively activated by properly driving the magnon mode with a magnetic field, which can be experimentally realized by directly driving the YIG sphere with a small MW loop antenna [34], allowing to implement the magnomechanical beamsplitter or two-mode squeezing interactions. Other quantum effects like tripartite Einstein-Podolsky-Rosen steering have also been studied [35]. In addition, many other interesting topics have been explored in CMM, including magnetically tunable slow light [36], phonon lasing [37], thermometry [38], and parity-time-related phenomena [39][40][41].…”
Section: Introductionmentioning
confidence: 99%
“…Again, the nonlinearity caused by the magnetostrictive interaction between magnons and phonons is crucial to maintain the robustness of this entangled state. Tan [326] identified both bipartite and tripartite EPR steering in such a hybrid system and found that continuous measurement of the cavity fields significantly enhances the bipartite steering.…”
Section: Magnon-photon Entanglementmentioning
confidence: 99%
“…In recent years, the analogous cavity magnomechanical system has received considerable attention [20,21]. It has been shown that cavity magnomechanics (CMM) has the potential to prepare macroscopic quantum states [22][23][24][25][26][27][28][29][30][31] and nonclassical states of microwave fields [32,33], and it has also promising applications in quantum information processing and quantum technologies [34][35][36][37][38][39][40][41][42][43]. In the CMM, a magnon mode (spin wave) couples to a deformation vibration mode of a ferromagnet (or ferrimagnet) via the magnetostrictive force, and to a microwave cavity mode via the magnetic dipole interaction.…”
Section: Introductionmentioning
confidence: 99%